The MAPKKK and MAPKK gene families in banana: identification, phylogeny and expression during development, ripening and abiotic stress - Lianzhe Wang (Nature Portfolio, 2017)
Abstract The mitogen-activated protein kinase (MAPK) cascade, which is a major signal transduction pathway widely distributed in eukaryotes, has an important function in plant development and stress responses. However, less information is known regarding the MAPKKK and MAPKK gene families in the important fruit crop banana. In this study, 10 MAPKK and 77 MAPKKK genes were identified in the banana genome, and were classified into 4 and 3 subfamilies respectively based on phylogenetic analysis. Majority of MAPKKK and MAPKK genes in the same subfamily shared similar gene structures and conserved motifs. The comprehensive transcriptome analysis indicated that MAPKKK-MAPKK genes is involved in tissue development, fruit development and ripening, and response to abiotic stress of drought, cold and salt in two banana genotypes. Interaction networks and co-expression assays demonstrated that MAPK signaling cascade mediated network participates in multiple stress signaling, which was strongly activated in Fen Jiao (FJ). The findings of this study advance understanding of the intricately transcriptional control of MAPKKK-MAPKK genes and provide robust candidate genes for further genetic improvement of banana.